2019
DOI: 10.1111/vru.12790
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐18‐fluoro‐2‐deoxy‐d‐glucose PET‐CT aids in detection of soft‐tissue injuries for dogs with thoracic or pelvic limb lameness

Abstract: Fluorine-18-fluoro-2-deoxy-D-glucose positron emission tomography (FDG PET) provides physiologic images of tissues based on their glucose metabolism. The combination of FDG PET and CT (FDG PET-CT) has been utilized in human musculoskeletal imaging to localize soft tissue lesions, however, this modality has not been thoroughly investigated for the diagnosis of canine lameness. This prospective, descriptive study evaluated FDG PET-CT findings in 25 client-owned dogs with inconclusive origin of thoracic or pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
8
1
1
Order By: Relevance
“…Thus, the interpretation of SUVs around oral structures should be assessed carefully to avoid tumor misdiagnosis. A previous study on dogs with limb lameness reported the SUVs of regions with (SUVmax > 1.0) or without (SUVmax < 1.0) pathologies (36). Also, previously reported SUVmax of normal skeletal muscles in dogs was ∼1.0 (4, 5), and these findings are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the interpretation of SUVs around oral structures should be assessed carefully to avoid tumor misdiagnosis. A previous study on dogs with limb lameness reported the SUVs of regions with (SUVmax > 1.0) or without (SUVmax < 1.0) pathologies (36). Also, previously reported SUVmax of normal skeletal muscles in dogs was ∼1.0 (4, 5), and these findings are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Also, previously reported SUVmax of normal skeletal muscles in dogs was ∼1.0 (4, 5), and these findings are consistent with those of the present study. As a diagnostic modality, FDG PET-CT could be valuable in detecting soft tissue abnormalities, which cannot be diagnosed by conventional means (36). However, in the present study, most of the SUVmax of skeletal muscles in normal cats were higher than 1.0.…”
Section: Discussioncontrasting
confidence: 61%
“…In this report the evidence of polyostotic osteomyelitis sustained by Serratia was also peculiar [ 2 , 3 , 4 , 5 , 6 , 7 ], compared to the greater evidence in the literature of monostotic osteomyelitis [ 24 ]. First-line therapy with amoxicillin/clavulanic acid was not targeted towards the specific microorganism and thus it was ineffective.…”
Section: Discussionmentioning
confidence: 91%
“…Septic polyostotic osteomyelitis is a rare bone infection in dogs, involving multiple bones and commonly caused by a long-term or persistent infection with fungal or bacterial agents [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Generally, a wide range of microorganisms could cause osteomyelitis, with bacterial infections being most frequently reported [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Badanie PET/CT ma również zastosowanie w wykrywaniu źródeł gorączki nieznanego pochodzenia, a także trudnych do zdiagnozowania kulawizn spowodowanych urazami, zmianami infekcyjnymi czy procesami nowotworowymi, szczególnie w obrębie tkanek miękkich (12,17,44,53). Dostarcza cennych informacji czynnościowych i anatomicznych związanych ze źródłem zapalenia lub zwiększoną aktywnością metaboliczną tkanki (17).…”
unclassified